SERVICE INNOVATION PADA HOTEL SANTIKA MATARAM - Muhammad Rahmatul Burhan; Muhammad Ali (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
A changing and hyper competitive market environment is necessary for hotel companies to provide superior services needed by consumers. This study aims to determine service innovations at the Santika Hotel Mataram. This research was designed using a qualitative approach.. After being analyzed using the Interactive Model, the results of the study showed that four dimensions of service innovation had been applied by the Hotel Santika Mataram. Technology plays an important role as a facilitator in the application of service innovations at Hotel Santika Mataram.Keywords:Hotel; Service Innovation; Marketing; Technology